2017
DOI: 10.1002/lt.24847
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric liver transplantation for hepatocellular cancer and rare liver malignancies: US multicenter and single‐center experience (1981‐2015)

Abstract: A tenth of all pediatric liver transplantations (LTs) are performed for unresectable liver malignancies, especially the more common hepatoblastoma (HBL). Less understood are outcomes after LT for the rare hepatocellular carcinoma, nonhepatoblastoma embryonal tumors (EMBs), and slow growing metastatic neuroendocrine tumors of childhood. Pediatric LT is increasingly performed for rare unresectable liver malignancies other than HBL. We performed a retrospective review of outcomes after LT for malignancy in the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
55
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 25 publications
10
55
1
Order By: Relevance
“…Another single‐institution experience with LT in 10 children with HCC, in which 70% exceeded MC, demonstrated a 5‐year OS of 83.3% . Several additional studies have continued to demonstrate good transplant outcomes in children with HCC who exceed MC, highlighting the need for distinct pediatric criteria . In our study, 71% (5/7) of patients that were transplanted exceeded the original MC (Table ), and all seven remain alive and cancer free.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Another single‐institution experience with LT in 10 children with HCC, in which 70% exceeded MC, demonstrated a 5‐year OS of 83.3% . Several additional studies have continued to demonstrate good transplant outcomes in children with HCC who exceed MC, highlighting the need for distinct pediatric criteria . In our study, 71% (5/7) of patients that were transplanted exceeded the original MC (Table ), and all seven remain alive and cancer free.…”
Section: Discussionsupporting
confidence: 55%
“…24,35,36 However, the MC have been criticized as being too strict; several studies have demonstrated good outcomes with more liberal criteria. [37][38][39][40] 13,17,32 In our study, 71% (5/7) of patients that were transplanted exceeded the original MC (Table 2), and all seven remain alive and cancer free.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…These findings have led to recent interest in LT even for some resectable cases of HCC . In an analysis of pooled SRTR data from 1987‐2015, Vinayak et al noted 1‐ and 5‐year OS of 85% and 51.7%, respectively. Our contemporary data show that outcomes of LT have dramatically improved over time to 1‐ and 5‐year OS of 94.7% and 80.8% and are now equivalent with HB.…”
Section: Discussionmentioning
confidence: 99%